‘No One Learned': Interpreting a Drugs Crackdown Operation and its Consequences Through The ‘Lens' of Social Harm - Mason, Will (The British journal of criminology, 2020)
This article seeks to extend studies of social harm by detailing the ways that harm is interpreted, identified and reflected upon by social actors in a specific empirical context: a drugs crackdown operation in a northern English city. Using a longitudinal ethnographic approach, unique insights are reported both from the time that the operation took place and a point in time five years afterwards. The data offer rich accounts of the immediate, short- and longer-term impacts as interpreted by youth workers and a group of mostly Somali young people (aged 13-19). Social harm, it is argued, offers a useful ‘lens' through which to critically explore the culpability of well-meaning state interventions in the (re)production of structural inequalities.